TP-YOLO: A Lightweight Attention-Based Architecture for Tiny Pest Detection - Di, Yang; Phung, Son Lam; Van Den Berg, Julian; Clissold, Jason; Bouzerdoum, Abdesselam (2023 IEEE International Conference on Image Processing (ICIP), 2023)
Automatic detection of agricultural pests is a challenging problem that is of great interest in biosecurity and precision agriculture. The detection model must cope well with the dense distribution of small-sized pests in complex backgrounds. This paper proposes a lightweight attention-based network, called TP-YOLO, for tiny pest detection. We introduce two attention-based components, namely Contextual Transformer and Omni-Dimensional Dynamic Convolution modules, to enhance feature extraction. The proposed modules are integrated into the YOLOv8 backbone, a state-of-the-art baseline for object detection. This paper also introduces a new benchmark dataset consisting of 1,600 images of Khapra beetles for objective evaluation of pest detection algorithms. Extensive experiments on two datasets indicate that TP-YOLO achieves competitive detection accuracy while having a significantly smaller model size and fast prediction time. We have made the code available to the public at: https://github.com/yangdi-cv/TP-YOLO.